Estrategia de superación tecnológica docente para el proceso de enseñanza aprendizaje en el nivel de educación básica del centro educativo Ing. “Alfonso Coronel” del barrio Trapichillo cantón Catamayo durante el periodo 2012 – 2013 - Santos Montaño, Elvia Alejandrina (2015)
This research has been developed in the educational center "Mr. Alfonso Colonel" TrapichilloCatamayo canton neighborhood, and Loja province the general objective was oriented in designing a strategy for overcoming technological teaching for the teaching-learning process at the level of basic education. The methods used for research development were: the scientific method by means of which developed throughout the research process from the formulation of the problem, the approach of the hypothesis, the implementation of instruments the analysis and interpretation of results, the deductive method that facilitated starting from the generality of the problem until you get to know their specificity or peculiarity of the same the analytic-synthetic method used accordingly to the systematization of the results, the survey was the main technique applied to teachers. As main result we could determine that the level of matter.